ASSESSMENT OF WATER QUALITY PARAMETERS OF THE TASHLYK COOLING POOL - Dudar, Tamara V.; Lysychenko, Georgy V.; Tatarchenko, Olena S. (Proceedings of National Aviation University (archive), 2008)
Data on hydrochemical monitoring parameters and water quality for the South-Ukrainian Nuclear Power Plant cooling pool are considered in the paper. Changes in the Tashlyk cooling pool water physical and chemical parameters under influence of the South-Ukrainian Power Complex are analyzed. It was shown that values of some parameters exceed limited acceptable concentrations for water reservoir for fish economy.